Pengaruh Pengetahuan Perpajakan, Sanksi Perpajakan,dan Sosialisasi Perpajakan terhadap Tingkat Kepatuhan Wajib Pajak Orang Pribadi: Bukti Empiris Pada Kp2kp Wonogiri - Reva Evia Noraida; Hudi Kurniawanto (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of tax knowledge, tax sanctions, and tax socialization on individual taxpayer compliance. The research was conducted at the Tax Service, Counseling, and Consultation Office (KP2KP) Wonogiri using a quantitative approach. Primary data were collected through questionnaires, and secondary data were obtained from relevant sources. A sample of 100 respondents was selected using a random sampling method. Data analysis was conducted using multiple linear regression techniques processed through SPSS 30. The results indicate that tax knowledge, tax sanctions, and tax socialization have a positive and significant effect on individual taxpayer compliance. These findings suggest that a higher understanding of tax regulations, stricter enforcement of sanctions, and more effective tax socialization efforts lead to greater taxpayer compliance.